GLOBAL WARMING - Rahmonova Muhayyohon Inomjonovna (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Annotation. This article provides a comprehensive overview of global warming, focusing on its causes, effects, and potential solutions. The discussion is structured into several sections, including an introduction, literature analysis, methods, results, discussion, conclusions, and suggestions.